Glucocorticoid therapy in chronic inflammatory bowel disease : from basic principles to rational therapy : proceedings of the International Falk Workshop held in Strasbourg, France, 5 September, 1993 - Möllmann, Helmut W; May, Burkard (Kluwer Academic, 1996)
The publication contains the proceedings of a workshop that focused on the use of glucocorticoids in the treatment of inflammatory bowel diseases. Intended for professional public.
Falk symposium series ; 73B
Keywords: antiflogistika; Inflammatory Bowel Diseases; idiopatické střevní záněty; farmakoterapie; Anti-Inflammatory Agents; gastroenterologie; Glucocorticoids; glukokortikoidy